THE ROLE OF PARENTS DURING THE CHILDREN LEARNING FROM HOME - Sulton Akbar (Citra Dharma Cindekia, 2022)
The policy of learning from home during the pandemic has restored the nature of parents as the main educators for children. The role of parents is needed and has a big impact on the success of children during the learning process from home. The method used in this research is a qualitative method by conducting a narrative review. The results of the review show that there are 13 things that parents can do while their children are studying from home, including ensuring their children live a clean and healthy life, accompanying children in doing schoolwork, doing activities together while at home, creating a comfortable learning atmosphere for children, establishing good communication accompanies children playing, exemplifies good things, performs supervisory functions, finances and fulfills family needs, and guides and motivates children, provides education, maintains religious values, carries out innovative and creative home activities.